Fotocatalisadores de dióxido de titânio dopados com metais de transição: síntese, caracterização e aplicação na fotodegradação de fármacos - AZEVEDO, Carla Arnaud de (Universidade Federal do Pará, 2025)
Heterogeneous photocatalysis has shown promise in ecological remediation and in the adequate treatment of pharmaceuticals as emerging contaminants. This study evaluated the photocatalytic activity of materials synthesized from the modification of the TiO₂ surface with transition metals (copper and cobalt) at concentrations of 0.5% and 1.5%, analyzing the physical, chemical and textural properties of the materials by N2 physisorption (BET) analysis, X-ray diffractometry (XRD), scanning electron microscopy–energy-dispersive X-ray spectrometry (SEM-EDS) and Fourier transform infrared (FT-IR). The experimental tests were carried out in an annular photoreactor with UV mercury lamp, following the Box-Behnken design, to evaluate the influence of catalyst mass (50 – 150 mg.L-1 ), drug concentration (2 – 8 mg.L-1 ) and irradiation time (60 – 120 min) on the photodegradation of acetaminophen (ACT) and diclofenac sodium (DCF). The BET results indicated that the materials have a mesoporous structure with an average pore diameter of 14.52 nm. XRD characterization confirmed the mixed structure of anatase and rutile and the absence of metal oxide peaks. The SEM-EDS analysis revealed irregular surfaces formed by misshapen grains and small particles attributed to metal oxides. The FT-IR showed O-H and Ti-O stretching bands, characteristic of photocatalytic materials. The FTCu1.5 photocatalyst was chosen for use in the photodegradation tests of the drugs due to its surface area, porosity and good anatase and copper content. The photocatalysis tests, in comparison with the photolysis tests, showed superior results, evidencing the functionality of the photocatalyst used. The degradation percentages reached 100% for both drugs and the concentration of the pollutant solution had a negative effect on the response variables, indicating that degradation increases with the reduction of the initial concentration of this solution. The proposed polynomial models presented a coefficient of determination (R²) > 0.9 and good predictive capacity. The Response Surface Methodology (RSM) and Desirability Function analyses indicated that it is possible to obtain a substantial reduction in the amount of photocatalyst used, when combined with an adequate adjustment in the irradiation time. The optimal conditions within the experimental domain for ACT are mcat = 100 mg.L-1 , CFA = 2 mg.L-1 and tIRR = 75 minutes, resulting in EffACT(%) = 99.05% and for DCF, the optimal conditions were mcat = 72 mg.L-1 , CFA = 2 mg.L-1 and tIRR = 65 minutes, resulting in EffDCF(%) = 90.39%. The developed photocatalyst significantly degraded the drugs and demonstrated promise for photocatalysis applications.